Efektivitas Peran Audit Internal Syariah: Studi Literatur Terbatas - Lukman Hakim (Universitas Muhammadiyah Jakarta, 2021)
The Islamic financial Institutions (IFI) governance structure required an internal shariah auditors to assist the duties of Shariah Supervisory Board (SSB). Internal audit was a key player besides SSB, External auditors and the Audit and Governance Committees (AGC). This study was to examine the effectiveness of the role of internal shariah auditors. By adopting limited literature review of indexed international journals was used in this study. The result of the study based on limited literature data sources were the effevtiveness of internal shariah audit on internal audit organizations ini the Good Corporate Governance (GCG) structure, namely the structure, requirements and processes of internal shariah audit. In addition, internal and external factors also affected the effectiveness of internal shariah audit. The Role of the AGC affected the effectiveness of internal audit. Governance and internal audit of Shariah non compliant income were important parts of risk management in IFI